2015
DOI: 10.3844/ajassp.2015.644.649
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Technical Efficiency of Sugarcane Production among Small Holder Farmers in Lao PDR

Abstract: This study was to examine technical efficiency in sugarcane production in Savannakhet, Lao PDR. A stochastic frontier production function was applied with the data collected from 110 sample farmers in 2012. The results reveal that cultivated area (p<0.01), hired labor (p<0.10) and capital (p<0.10) are the major significantly positive factors in the output of sugarcane. Mean of technical efficiency was found to be 0.7431. In order to increase the efficiency of sugarcane farms improvements in farmers' education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
3
0
1
Order By: Relevance
“…Education plays a great role in adoption of most new technologies that normally calls for better management including consistent record keeping and proper use of the various inputs in sugarcane (Kibirige, 2008). The results of the current study conforms to Muhammad (2015), Supaporn (2015), Kibirige et al (2014), Thabethe et al (2014, Ali et al (2013) and Kibirige (2013)'s findings where educational level of a farmer was positively related to technical efficiency. However, Padilla-Fernandez and Nuthall (2001) found educational level of a farmer to be a weak predictor of technical efficiency while Kibirige et al (2016) found educational level of a farmer to be negatively related to technical efficiency.…”
Section: Factors Affecting Production Efficiencysupporting
confidence: 91%
See 1 more Smart Citation
“…Education plays a great role in adoption of most new technologies that normally calls for better management including consistent record keeping and proper use of the various inputs in sugarcane (Kibirige, 2008). The results of the current study conforms to Muhammad (2015), Supaporn (2015), Kibirige et al (2014), Thabethe et al (2014, Ali et al (2013) and Kibirige (2013)'s findings where educational level of a farmer was positively related to technical efficiency. However, Padilla-Fernandez and Nuthall (2001) found educational level of a farmer to be a weak predictor of technical efficiency while Kibirige et al (2016) found educational level of a farmer to be negatively related to technical efficiency.…”
Section: Factors Affecting Production Efficiencysupporting
confidence: 91%
“…Age represents general decision making ability and knowledge of production process. Farmer's age is accepted to have great contribution towards personal learning, personality development, attitude and skills with correct judgment (Supaporn, 2015;Muhammad, 2015;Kibirige et al, 2014;Aung, 2012;Ayaz & Hussain, 2011). Thabethe et al (2014) argued that older farmers appear to be more efficient than younger farmers because of their good managerial skills, which they had learnt over time.…”
Section: Factors Affecting Production Efficiencymentioning
confidence: 99%
“…Research on farming efficiency (technical efficiency, allocative, and economic) have been carried out in various regions in Indonesia and the world. The range of technical efficiency, allocative and economic in various studies are relatively diverse, but Bakhsh et al (2006); Kea et al (2016); Singh et al (2018) ;Supaporn, (2015); Mutenheri et al (2017) found that the level of efficiency of farmers amounted to 0.70 can be said to have efficient, while Coelli et al (1998) stated that the level of farmer efficiency of 0.80 can be said to have been efficient. Sugarcane production efficiency study in East Java was conducted by Susilowati and Tinaprilla, (2012); Purnamasari et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The TFP growth is claimed to contribute negligibly to the output growth by merely 0.03% points (p. 64). As mentioned, there are more studies on agriculture that have applied the frontier and inefficiency model, including Boundeth et al (2012) and Viengpasith et al (2012) in the case of maize; Supaporn (2015) in the case of sugarcane; Soukkhamthat and Wong (2016) in the case of cassava; and Inthavong (2005), Phetsamone (2012), and Sayavong (2018) in the case of rice production. Since this study was focused solely on the manufacturing industry, these have not been included in the review.…”
Section: Literature Reviewmentioning
confidence: 99%